The Influence of Person-Job Fit on Work Engagement and Turnover Intention, Mediated by Work-Family Conflict and Family-Work Conflict among State-Owned Banks Employees in Jakarta - Yulita Suryantari; Andy Mulyana; Nihan Anindyaputra Lanisy; Ni Wayan Marsha Satyarini (Kontigensi : Jurnal Ilmiah Manajemen, 2023)
The banking industry has serious issues related to human resources, such as the high employee turnover rate and work engagement of employees in the work environment. This research aims to analyze the influence of person-job fit on work engagement and turnover intention on employees of state-owned banks in Jakarta by using work-family conflict and family-work conflict as mediating variables. The samples used in this research were taken from 320 frontline employees of state-owned banks in Jakarta including Bank Mandiri, Bank BRI, Bank BNI and Bank BTN. The data were collected by using non-probability sampling with purposive sampling method. The data analysis used in this research is structural equation modeling. The results of this research show that there are both negative and positive influences between each variable, and work-family conflict and family-work conflict as mediating variables proved to have an effect on person-job fit on work engagement and turnover intention. This research has several implications for bank managers to be more selective in recruiting employees in order that person-job fit can be met, to make a personal approach to each employee, to pay attention to the employees' capacity and rights, and to hold periodic training for employee.